The development of a fixed wing aircraft analysis and design flight dynamic software - Ahmad Alaian, Ahmad Eshtiwey (2016)
The present work focused on the development of computer software for flight dynamic analysis and controlling the behavior of a fixed-wing aircraft. For a given aircraft geometry, mass and inertia properties, and flight conditions, the software was designed in such a way to start the estimation of aerodynamic characteristics, trimmed flight, stability analysis through linearized approach as well as non-linearized, and finally the control design of the flying behavior by using PID controller method. The estimation of aerodynamic characteristics used the semi-empirical aerodynamic method as used by Roskam. The trimmed flight conditions were solved through trimmed flight equations iteratively. The linearized form of flight dynamic equations in longitudinal as well as in lateral direction were solved using the transfer function approach and state-space method. Whilst, non-linear flight dynamic equations were solved using the Simulink. Three different PID controller designs were developed to control the aircraft to follow a particular flight behavior. The developed computer code was written in MATLAB programming language and grouped into several modules. The validation results were carried out by comparing the results of each module to other results available in the literature. The developed computer code was applied to the case of five aircraft. They were named Cessna 182, Cessna 310, Piper Cherokee PA 28-162, Learjet 24, and Cessna 620. The first three aircraft were propeller piston engine aircraft. The fourth aircraft was a jet engine aircraft while the fifth aircraft represented a turboprop aircraft. The flight dynamics behavior motion which consisted of 22 flight variables were obtained by solving the governing equation of flight after the aerodynamic characteristics data were established and the trimmed fight conditions were solved. A particular flight variable can be set up to have a particular behavior that follows the movement of the control surface operations. Various control surface movements were simulated to ensure the designed PID controller was really providing a particular flight behavior. Through the implementation of five types of aircraft models, the developed computer code represents a useful tool for flight dynamic analysis and control design for a fixed-wing aircraft.